Hofmeister effects of anions on self-assembled thermogels. (March 2022) - Loh, W.W.; Lin, Q.; Lim, C.C.; Guo, L.; Tang, Y.K.; Loh, X.J.; Lim, J.Y.C.
Abstract: Thermogels are temperature-responsive soft biomaterials with numerous biomedical applications. They possess high water content and can spontaneously gelate by forming non-covalent physical crosslinks between their constituent amphiphilic polymers when warmed. However, despite the ubiquity of salts in biological fluids and buffer media, the influence of salts on thermogelling polymers and the overall physical properties of the resulting hydrogels are poorly understood. Herein, we elucidate the effects of common inorganic salts on the gelation and micellization properties of a thermogelling polymer containing poly(ethylene glycol), poly(propylene glycol), and poly(caprolactone) components. The identity of the salts' anions and their concentrations was found to exhibit significant effects on the thermogel properties, in some cases being able to decrease the sol-to-gel phase transition by up to 10 °C. We demonstrate that these notable influences are likely brought about by the changes in solvation of both the polymer's hydrophobic and hydrophilic segments, as well as by direct interactions of poorly hydrated anions with the hydrophobic polymer segments. Our findings show that the effects of salts on amphiphilic thermogelling polymers are non-negligible and hence need to be taken into account for engineering and optimization of thermogel properties for different biomedical applications. Highlights: The properties of temperature-responsive hydrogels were influenced by anions more than cations. Chaotropic anions raised gelation temperature and formed weaker gels. These effects resulted from changes to polymer hydration and direct polymer-anion interactions. Anions also affected the micellization behavior of the amphiphilic polymers in water. Effects of salts need to be taken into account in thermogel formulations for various applications.